Global concerns for forest resource utilization : sustainable use and management : selected papers from the International Symposium of the FORESEA Miyazaki, 1998 - International Symposium of the FORESEA Miyazaki (1998); Yoshimoto, Atsushi; Yukutake, Kiyoshi (Dordrecht, The Netherlands : Kluwer Academic Publishers, 1999)
28